2019
DOI: 10.1017/s0033291719002034
|View full text |Cite|
|
Sign up to set email alerts
|

Symptom structure of PTSD and co-morbid depressive symptoms – a network analysis of combat veteran patients

Abstract: Background Despite extensive research, symptom structure of posttraumatic stress disorder (PTSD) is highly debated. The network approach to psychopathology offers a novel method for understanding and conceptualizing PTSD. However, extant studies have mainly used small samples and self-report measures among sub-clinical populations, while also overlooking co-morbid depressive symptoms. Methods PTSD symptom network topology was estimated in a sample of 1489 treatment-seeking veteran patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 168 publications
(373 reference statements)
9
59
2
Order By: Relevance
“…In both pre-treatment networks, flashbacks emerged as most influential while amnesia had the least expected influence. Overall, the results were comparable to network analyses of similar samples [29,30]. The NetworkCom-parisonTest revealed that the structure of the Clinician Administered PTSD Scale and PTSD Checklist network both changed from pre-to post-treatment (both p < .001), which was supported also by the results of the community analyses (see Additional file 1: TableS2).…”
Section: Ptsd Network and Node Metricssupporting
confidence: 71%
See 3 more Smart Citations
“…In both pre-treatment networks, flashbacks emerged as most influential while amnesia had the least expected influence. Overall, the results were comparable to network analyses of similar samples [29,30]. The NetworkCom-parisonTest revealed that the structure of the Clinician Administered PTSD Scale and PTSD Checklist network both changed from pre-to post-treatment (both p < .001), which was supported also by the results of the community analyses (see Additional file 1: TableS2).…”
Section: Ptsd Network and Node Metricssupporting
confidence: 71%
“…Consequentially, there was no missing data among the included participants. Participant characteristics are outlined in Table 1 (for a more detailed description of the original dataset, see [29]). The study was approved by the Ethics Committee of the IDF Medical Corps.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the fast-expanding research fields focused on identifying associations between a wide array of symptoms and other factors, and commonly utilizing network models, is the field of post-traumatic stress. Over the past half-decade, numerous studies investigating associations between symptomatology (Mcnally et al, 2015;van Loo et al, 2018), potential risk factors (Armour et al, 2017;Choi et al, 2017;Mancini et al, 2019;Simons et al, 2019) and pathways to comorbidity (Djelantik et al, 2020;Gilbar, 2020;Lazarov et al, 2019;Malgaroli et al, 2018;Price et al, 2019;Vanzhula et al, 2019) have been published and yielded novel results and hypotheses. In response to this rapid research expansion and in an aim to synthesize current findings in the field, a thorough systematic review of the network approach to posttraumatic stress disorder (PTSD) has been recently carried out (Birkeland et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%